The Effect of National Public Debt on Economic Growth in Kenya - Hassan, Mohamedamin Ahmed; Ongeri, B. Onkoba; Ndolo, David Katuta (European Scientific Journal, ESJ, 2023)
Kenya being a lower middle income country compliments tax revenue with government borrowing to finance its national development plans. In an attempt to add to available domestic resources, successive governments have relied on both domestic and external debt to finance the country’s budget. In light of the growing concerns over Kenya’s national public debt sustainability and its potential effect on the economy, this study aimed at analyzing the effect of national public debt on economic growth in Kenya. Specifically, the study sught to establish the effect of domestic debt and external debt on Kenya’s economic growth. Gross Domestic Product was used as the proxy for economic growth while domestic debt, external debt, inflation rate, exchange rate, capital stock and labor force are the explanatory variables. The study used time series data for the period 990 to 20 9. The data was extracted from the World development indicators and this data was harmonized with data extracted from the data bases of the Kenya National Bureau of Statistics. The data was analyzed through the Ordinary Least Square (OLS) regression technique. The findings indicated that domestic debt had an insignificant negative effect on Kenyan economy while external debt has insignificant positive effect. The study concluded that internal debt has deleterious while external debt has positive effect on growth.